Analysis of Forest Cover in the Tumba-Lediima Nature Reserve (RTL-DRC) - Frey, Sylvestre; Musas, André Musas A; Kibamba, Nestor Anzola; Mboma, Sebastien Kidushi; Simboni, Tege Simboni; Asidi, Djonive Munene (Indonesian Journal of Earth Sciences, 2025)
This study analyzes the evolution of forest cover in the Tumba-Lediima Nature Reserve between 2010 and 2022, a period marked by increasing anthropogenic pressures.  The main drivers of deforestation identified are agricultural expansion, illegal exploitation of forest resources and urbanization. These activities have led to the fragmentation of critical habitats, putting endemic and threatened species at risk, while also compromising the ecological integrity of the reserve. Furthermore, local communities face diminished livelihoods due to reduced access to natural resources. These dynamics lead to a critical loss of biodiversity, affecting critical habitats and compromising the livelihoods of local communities. Using Landsat 7 and 8 satellite imagery, combined with NDVI calculation and supervised classifications validated by a high Kappa coefficient, this study provides an accurate mapping of land cover change. The results reveal an alarming reduction in primary forest cover, accompanied by an increase in secondary forests and fallow land, suggesting limited potential for regeneration. This pattern underscores the urgent need to address the drivers of deforestation through targeted actions. These trends call for urgent conservation measures, including the targeted regeneration of degraded areas, the strengthening of environmental laws and the integration of local communities in the sustainable management of resources. By proposing concrete strategies in the short, medium and long term, this study offers essential perspectives for preserving the biodiversity and ecological resilience of the reserve. By proposing actionable strategies in the short, medium, and long term, this study provides a roadmap for preserving not only the biodiversity and ecological resilience of the reserve but also offers scalable solutions for similar tropical forest regions facing comparable challenges.